Formación para la detección de la violencia de género durante el embarazo: evaluación de una propuesta contextualizada - Montserrat Payá-Sánchez; Analía Gómez-Fernández; Julia Martín-Badia; Josefina Goberna-Tricas (Universitat de Barcelona, 2019)
Introduction: Intimate partner violence is a terrible reality that is present in all countries. When it involves a pregnant woman, the negative effects multiply affecting also the fetus. Improving the procedures for detection and treatment is one of the measures that will allow to eventually overcome intimate partner violence. Because of the functions that midwives perform during pregnancy, monitorization, and post-partum, and because of the relationship of trust they establish with the pregnant woman, midwives are in a particularly suitable position to proceed with their detection. Materials and Method: In this article we present the objectives, contents and evaluation of a training activity aimed at midwives of the municipality of Hospitalet de Llobregat that took place this year in the context of a Participatory Action Research that aims to improve the detection and approach of cases of intimate partner violence during pregnancy. Results: The results of the training activity's assessment report favorably on its repetition and point, for its improvement, to the realization of more activities focused on the application of contents and to increase the training received on services of attention to women in contexts of intimate partner violence, circuits of referral, and emotional intelligence. Discussion and Conclusions: The assessment has focused on the activity's formative nature. The objectives and the impact of the activity have been evaluated. In accordance with the Participatory Action Research, we have chosen a horizontal and participatory approach. Promoting training actions and submitting them to evaluation is one of the ways to combat intimate partner violence.